Case report: painful exanthems caused by enterovirus D68 in an adolescent. Issue 33 (August 2019) - Chang, Tu-Hsuan; Yang, Tzu-I; Hsu, Wei-Yun; Huang, Li-Min; Chang, Luan-Yin; Lu, Chun-Yi
Abstract: Rationale: Unlike other enteroviruses which can cause herpangina or hand-foot-and-mouth disease, enterovirus D68 (EV-D68) has usually been linked to respiratory and neurological problems in young children. Skin manifestations had rarely been described in current literatures. Patient concerns: We report a 17-year-old girl with fever and painful skin rash over legs and soles for 9 days. Pitting edema was also noted below the knees. There was no respiratory tract or neurological symptoms in this patient. Diagnoses: EV-D68 was detected from a throat swab by RT-PCR and confirmed to be subclade B3 by sequencing. Interventions: Supportive management. Outcomes: The patient was afebrile after 9 days and got full recovery on the 23rd day at outpatient follow-up. Lessons: To the best of our knowledge, this is the first report of EV-D68 infection with skin manifestations, clinical images, and detailed clinical course. Our findings in this particular case extend the understanding of the disease spectrum.